An alternative model for supporting the rice farmers in adaptation of climate change - Rafia, Afroz (Econ journal, 2017)
In Malaysia, the contribution of agriculture has been declining at 8.9% in 2000 and 8.2% in 2005. Because the climate is changing and farmers have to confront a number of barriers to adaptation to climate change. Primary data are received from the survey questions administered in Kedah, Malaysia and analyzed to investigate farmers’ intention to use the proposed integrated waqf environmental protection model by adopting the theory of reasoned action. Based on the responses received from the field, it has been shown that the attitude of the farmers significantly affects farmers’ intention to use the proposed model.